Synthesis, antifungal activity and semi-empirical AM1-MO calculations of some new 4-oxo-4H-chromene derivatives - El-Shaaer, Hafez Mohamed; Abdel-Aziz, Salah Abdel-Ghaffar; Hanafy, Faten Ismail; Ali, Tarik El-Sayed; El-Fauomy, Ali Zaky (European Journal of Chemistry, 2011)
Some new antifungal agents have been prepared through reaction of 4-oxo-4H-chromene-3-carbaldehydes (1a,b) with some active primary amines (2a-e) and amides/thioamides (6a-d) in different conditions. Structures of the products were established on the basis of elemental analysis, IR, 1H NMR, mass spectra and semi-empirical AM1-MO calculations.